Randomized clinical trial of preoperative oral versus intravenous iron in anaemic patients with colorectal cancer. Issue 3 (16th January 2017) - Keeler, B D; Simpson, J A; Ng, O; Padmanabhan, H; Brookes, M J; Acheson, A G; Banerjea, A; Walter, C; Maxwell-Armstrong, C; Williams, J; Scholefield, J; Abercrombie, J; et al.
Abstract: Background: Treatment of preoperative anaemia is recommended as part of patient blood management, aiming to minimize perioperative allogeneic red blood cell transfusion. No clear evidence exists outlining which treatment modality should be used in patients with colorectal cancer. The study aimed to compare the efficacy of preoperative intravenous and oral iron in reducing blood transfusion use in anaemic patients undergoing elective colorectal cancer surgery. Methods: Anaemic patients with non-metastatic colorectal adenocarcinoma were recruited at least 2 weeks before surgery and randomized to receive oral (ferrous sulphate) or intravenous (ferric carboxymaltose) iron. Perioperative changes in haemoglobin, ferritin, transferrin saturation and blood transfusion use were recorded until postoperative outpatient review. Results: Some 116 patients were included in the study. There was no difference in blood transfusion use from recruitment to trial completion in terms of either volume of blood administered ( P = 0·841) or number of patients transfused ( P = 0·470). Despite this, increases in haemoglobin after treatment were higher with intravenous iron (median 1·55 (i.q.r. 0·93–2·58) versus 0·50 (−0·13 to 1·33) g/dl; P < 0·001), which was associated with fewer anaemic patients at the time of surgery (75 versus 90 per cent; P = 0·048). Haemoglobin levels were thus higher at surgery after treatment with intravenous than with oral iron (mean 11·9 (95 per cent c.i. 11·5 to 12·3) versus 11·0 (10·6 to 11·4) g/dl respectively; P = 0·002), as were ferritin ( P < 0·001) and transferrin saturation ( P < 0·001) levels. Conclusion: Intravenous iron did not reduce the blood transfusion requirement but was more effective than oral iron at treating preoperative anaemia and iron deficiency in patients undergoing colorectal cancer surgery. Abstract : No difference in transfusion requirements